Assessing job flows across countries : the role of industry, firm size and regulations - Haltiwanger, John C., 1955- 1955- (NBER working paper series, 2008)
"This paper analyzes job flows in a sample of 16 industrial and emerging economies over the past decade, exploiting a harmonized firm-level dataset. It shows that industry and firm size effects (and especially firm size) account for a large fraction in the overall variability in job flows. However, large residual differences remain in the job flow patterns across countries. To account for the latter, the paper explores the role of differences in employment protection legislation across countries. Using a difference-in-difference approach that minimizes possible endogeneity and omitted variable problems, our findings show that hiring and firing costs tend to curb job flows, particularly in those industries and firm size classes that require more frequent labor adjustment"--National Bureau of Economic Research web site